Sosialisasi Penggunaan Pestisida Nabati Untuk Pengendalian OPT Sayuran Hidroponik Pada Kelompok Wanita Tani Kirani - Kusumawardhani, Linda Octavia; Aryani, Gisca Sabrina Dwi; Syah, Mirza Andrian; Witjaksono, Gideon Setyo Budi (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Community service is one of the KKN-T MBKM program of East Java "Veteran" National Development University students. Growing vegetables hydroponically is of great interest to the community because it does not need to have a large area of ​​land, but hydroponic plants are susceptible to pests and diseases. Therefore it is necessary to apply plant-based pesticides to organically eradicate OPT in hydroponic plants, plant-based pesticides are made in order to create an environment that is safe from chemicals and produce fresh products. The purpose of this community service activity is to provide knowledge and skills in using vegetable pesticides from shallot skins to control OPT (Plant Pest Organisms) on hydroponic vegetables and to increase the activity of members of the “Kirani” Women Farmers Group (KWT) in optimizing their yards for farming. agribusiness development so that it can increase the household income of KWT members. Assistance to the Farmer Women's Group lasted for about three months together with students of the Faculty of Agriculture, East Java "Veteran" National Development University.